An investigation of some key physico-chemical water quality parameters of an Integrated Multi-Trophic Aquaculture (IMTA) system operating recirculation methodology in the Western Cape of South Africa - De Prisco, Joseph Anthony (Department of Oceanography, 2021)
Over the last few decades, Integrated Multi-Trophic Aquaculture (IMTA) in South Africa has developed from early experimental designs to large scale, commercially operating farms. This was in response to uncertainty regarding food availability for stock (primarily kelp in the case of abalone farms) and a desire to recirculate water whilst reducing the environmental footprint of the abalone farms. The growing prevalence of IMTA as a commercially viable activity has brought about a need for an expansion of the knowledge pool regarding the physico-chemical processes at work in such systems. Of particular interest to researchers are mechanisms and dynamics of nutrient transfer between components of the system and how these could be manipulated to increase efficiency and reduce running cost of farms. This work was conducted to try and quantify some of the changes in some physical and chemical characteristics of the water stream on a large-scale IMTA farm cultivating seaweed of the genus Ulva (Ulva rigida) and the locally named perlemoen abalone (Haliotis midae) on the south west coast of South Africa (Viking Abalone Farm at Buffeljagsbaai, Western Cape, South Africa) (34.7550° S, 19.6154° E). Experiment one was a three-day experiment taking place in December of 2018, there was no particular reason for the choice of month, analyses of this nature are potentially useful on any given day of any given month as although the literature contains plenty of gaps, there is no single identifiable data gap sufficient to encourage the use of particular timeframes. The sampling regime involved single sample point testing of three modular clusters each operating a different rate of water recirculation (50%, 75% and 100%) with 50% recirculation being standard farm operation, 75% and 100% tested to gauge effect of increasing recirculation, 75% tested as a potential standard farm operation to reduce load on pumps and reduce volumes of water pumped in, 100% tested in case of emergency situation which requires farm to be isolated from the inbound water stream arriving from the immediate coastal water, ambient conditions were also tested for reference and comparison. Parameters tested were those which the farmers already tested periodically to gauge changes in water quality which may effect the abalone or seaweed, though slightly different methods were used for the testing of ammonia. On the farm the standard method is the Nesler photometric test (Lovibond photometer), whereas this research was conducted using a calibrated indophenol blue spectrophotometric technique (Modified Grasshoff, 1976). Results showed no statistically significant differences (Mood's Median Test, p>0.05) between the 50% and 75% recirculation cluster for temperature, pH, Total Ammonia Nitrogen (TAN) or Free Ammonia Nitrogen NH3 (FAN). At 100% recirculation, statistically significant differences (Mood's Median Test, p0.05) occurred for temperature. At 100% recirculation, TAN and FAN increased rapidly, though the commensurate rapid and considerable decrease in pH meant the FAN increase was not as high in magnitude as it would be at 4 a normal seawater pH of around 8.2. Abalone suffered no mortalities at 100% recirculation for three days and later reports from the farmers suggested no noticeable drop in growth rate that could be attributed to this test in the months following the experiment. From the regulatory perspective, the TAN levels breached WWF guideline maximum effluent concentrations for abalone aquaculture (600µM/l) only in the 100% recirculation cluster, and only then during three of the thirteen sampling runs. The TAN concentrations in 50% and 75% recirculation treatments were far below the WWF guideline maximum effluent concentration with maximum concentrations of 7.15 µM/l in 50% and 13.46 µM/l at 75%, the increase in maximum concentration was large but not egregious and resulted from a more pronounced build-up of ammonia as residence time of water in the cluster increases at 75% recirculation. Experiment two was an intensive 24-hour sampling run; the primary aim was to test the effectiveness of the seaweed biofilter in an Integrated Multi-Trophic Aquaculture (IMTA) farm culturing perlemoen abalone and a green macroalga. Parameters tested were temperature, pH, dissolved oxygen, salinity, TAN, nitrate and nitrite as these are relevant parameters for the farmer and the necessary equipment to test them was available. Samples were stored in a freezer for this experiment due to intensity of sampling regime, and spiked standards were prepared to check shifts in concentration of TAN, nitrate and nitrite that may have resulted from the freezing and thawing processes. Spike recoveries were good in the case of TAN (87%-98%) and nitrite (92%-96%), but random and widely dispersed in the case of nitrate. As such, nitrate and nitrite were removed from the analysis as nitrite values only really held value if taken in conjunction with nitrate values. Minimal and non-useful variation in salinity observations meant that salinity was also discounted from the analysis. Temperatures varied minimally between sampling points during the experiment, though they rose in all sampling points during daytime as would be expected. pH was higher in abalone inbound and Ulva effluent water compared to the abalone effluent water. Total ammonia nitrogen percentage removal across the seaweed biofilters ranged from 65%-85% with the mean and median at 73% and 71% respectively. Free ammonia nitrogen percentage removal across the seaweed biofilters ranged from 41%-80% with the mean and median removals at 63% and 66% respectively. A regression analysis demonstrates a strong positive linear relationship between TAN removal and TAN load to the seaweed biofilter (r2= 0.90). Principal component analysis revealed a strong negative correlation between FAN removal and pH, as pH increased across the seaweed biofilters, the level of FAN removal decreased. This suggests that the perceived benefit of increasing pH in seaweed biofilters during the day-time may have some negative repercussions.